Age-dependent differences in type I interferon, IL-12 and pro-inflammatory cytokine production by porcine peripheral blood mononuclear cells in response to pseudorabies virus-infected cells - Claeys, Manon S. C.; Brabant, Simon G. A. L.; Rosschaert, Stijn; Van Waesberghe, Cliff; Favoreel, Herman W. (Frontiers in Immunology, 2025)
Pseudorabies virus is a porcine alphaherpesvirus that causes devastating disease with high mortality in young piglets but much milder, mainly respiratory, problems in older pigs. Here, we report marked age-dependent differences in the cytokine response profile of primary porcine peripheral blood mononuclear cells (PBMCs) to pseudorabies virus (PRV)-infected cells. Notably, IFN-α and IL-12 production in response to PRV remains low to almost undetectable in piglets up to 8.5 weeks of age, followed by a marked increase in older piglets, which coincides with age-related shifts in PRV symptomatology. Additionally, we found that PBMC from newborn piglets exhibit a high IL-6 and IL-10 production which, in combination with the low IL-12 levels, suggests a suppressed Th1 immune response, similar to neonatal humans and mice. Our results reveal a remarkable age-dependent difference in PBMC cytokine response to PRV and provide a basis to identify cytokines or adjuvants that shift the neonatal immune response towards a Th1 response, potentially improving outcomes of severe viral infections in the neonatal period in both pigs and humans.